Stress and Burnout among Emergency Department Staff Members: A Cross-Sectional Study - R, Monisha; Hamsa, Hemavathi; Sai Manjunath Swamy, V; Kumar Ravi Koralakunte, Pavan; Pai, Shantheri; M, Harshavardhan (Journal of Neonatal Surgery, 2025)
Background: Attributable to their frequent exposure to traumatic or life-threatening situations while performing their duties, as well as a variety of vulnerability factors, research has consistently shown the steadily rising rates of stress and instances of burnout among emergency department personnel. Persevering in such occupational conditions over a prolonged duration of time is proven to culminate in psychiatric as well as medical illness/es, often than not affecting the efficiency of their work. Materials and Method: A cross-sectional observational study was conducted among ED staff at a district general hospital over one month. Purposive sampling yielded 150 participants, including physicians, nurses, and support staff. Participants completed surveys assessing perceived stress (Perceived Stress Scale) and burnout (Maslach Burnout Inventory), and provided demographic and occupational data. Data analysis included descriptive statistics, chi-square tests, and correlation analyses. Results: Participants had a mean age of 34.2 years and average tenure of 8.5 years in the ED. High levels of stress were reported (mean Perceived Stress Scale score = 23.5, SD=6.4). Burnout was prevalent, with high rates of emotional exhaustion (68%), depersonalization (54%), and low personal accomplishment (42%). Key stressors included high workload, time pressure, emotional demands, and organizational factors, (inadequate staffing, poor work-life balance). Higher stress and burnout levels correlated significantly with lower job satisfaction, increased intention to leave, perceived lower quality of patient care, and higher rates of self-reported medical errors. Conclusion: Stress and burnout among ED staff significantly impact staff well-being and patient care quality. Effective interventions, (organizational support, provision of mental health resources, and resilience training programs), are essential to alleviate these issues and enhance job satisfaction and patient outcomes in ED settings.